(untitled) (Journal of the College of Education for Women, 2019)
This research has been written as a fullfillment of the researchersdesire of joining the qurannic convoy servos each one from his own place andthis own field of specialization . she has found that the holly quraan is aparctical field for theories and rules of old and modren phonetic studies alsoshe has becom a ware of the fact that the quraanic Important –making hasvarious aspects that neither can be a ware of nor can be vanished by thecourses of ages for science can flourish and reach tops to the extent theydon’t accept any new addition theories can be studied and given laws at lastexcept the quannice important – making which is new and discovered atdeferent times and places in spite of the shortness of surah al qadir it isconsidered as a practical domain for this reseach waich deals whth the soundas one aspect besides this paper meets with researchers direction to wardsquraand studies wether in her dissertation submitted to doctorate degree(ph.o) in her future papers.